The Use of Zakat Funds to Support the Government's Stunting Eradication Program from a Maslahah Mursalah Perspective - Fitrah Humairah; Syafruddin Syam (LP2M IAIN Palopo, 2026)
Stunting remains a serious problem in Indonesia because its prevalence has not yet reached the reduction target as stipulated in Presidential Regulation Number 72 of 2021. Zakat funds can be positioned as a complementary funding source to strengthen state intervention in stunting prevention. This study aims to analyze the use of zakat funds to support the government's stunting reduction program from a maslahah mursalah perspective. This study uses a normative juridical method with a statute approach and a conceptual approach. Data sourced from secondary data obtained through document studies include primary legal materials in the form of laws, as well as secondary legal materials in the form of law books, legal journals, and opinions of legal experts relevant to this study. The data were processed qualitatively and analyzed using deductive reasoning. The results of the study indicate that the use of zakat funds can support the government's stunting reduction program, particularly through the utilization of consumptive and productive zakat distributed to poor and needy Muslim families. The use of zakat funds for stunting reduction in Indonesia is currently not evenly distributed across all cities and districts. Based on the perspective of maslahah mursalah, the use of zakat funds for stunting reduction programs is permissible and highly relevant because it provides public benefit and is beneficial in preserving the soul (hifz al-nafs) and offspring (hifz al-nasl) without conflicting with sharia provisions. Therefore, strengthening regulations and cross-sectoral coordination is needed so that the use of zakat funds to support accelerated stunting reduction can be implemented in a more targeted, integrated, and sustainable manner.